Penyebaran Praktek Pertanian Baru oleh Opinion Leader (Faktor-Faktor yang Mempengaruhi Pengembangan Padi Sawah Organik) - Putu Arimbawa; Muhammad Aswar Limi; Sarinah Sarinah; Doddy Ismunandar Bahari; Yusriadin Yusriadin (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
The development of organic agriculture in Indonesia progresses slowly. The role of agricultural extension workers as farmer facilitators requires support from community opinion leaders. Opinion leaders have followers and influence within their communities, making their role crucial in accelerating the diffusion of innovation. This study aims to identify the characteristics and roles of opinion leaders by analyzing communication channels and the factors influencing the development of organic rice farming. The research employs a survey method with a questionnaire as the primary data collection tool. Data were gathered through interviews with 150 rice farmers and relevant stakeholders. In-depth interviews and observations were used to supplement the survey data. The research was conducted in East Kolaka Regency. Data were analyzed descriptively and using Structural Equation Modelling (SEM-PLS). Using diffusion theory, we identified 11 opinion leaders in the research area, characterized by their success in farming, experience, access to information, and openness. Opinion leaders maintain interpersonal relationships and are closely connected with other farmers. They serve as learning sources and consultation points for farmers in agricultural activities. Several factors influence the role of opinion leaders in the development of organic rice farming, including institutional characteristics, availability of demonstration plots, supporting factors, innovation characteristics, and the use of communication media. Therefore, agricultural extension workers should involve opinion leaders to accelerate the development of organic rice farming.